Unmasking Renal Complications of Immunotherapy: A Case of Nivolumab-induced FSGS - Khan, Urvashi; Jha, Lakshmi Kant; Tyagi, Pranav (Journal of Clinical Nephrology, 2025)
Immune Checkpoint Inhibitors (ICPIs), while revolutionizing cancer therapy through potentiation of anti-tumour responses via targeted blockade of T-lymphocyte inhibitory receptors, are associated with immune-related adverse events (irAEs), including diverse renal manifestations. This report presents a case of a 69-year-old male with urothelial carcinoma who developed Acute Kidney Injury (AKI) and nephrotic-range proteinuria following initiation of nivolumab, an anti-PD1 antibody, necessitating renal biopsy to clarify the aetiology. The biopsy revealed Focal Segmental Glomerulosclerosis (FSGS) with endotheliopathy, suggesting a direct ICPI-induced glomerular injury. This case underscores the need for heightened awareness of ICPI-associated glomerular disease, alongside more common renal adverse events such as Acute Interstitial Nephritis (AIN), and for the need for renal biopsy in such cases. While the incidence of ICPI-associated AKI is approximately 17%, and AIN is a more frequent finding, FSGS and other glomerular pathologies should also be considered. Current treatment for such renal events involves discontinuation of the ICPI agent and initiation of immunosuppression with glucocorticoids. The management of these cases requires prompt detection, timely diagnosis, and often interdisciplinary collaboration, thus highlighting the need for more case reports, research, and better treatment strategies.